2022
DOI: 10.1002/app.52957
|View full text |Cite
|
Sign up to set email alerts
|

Effect of compatibilizer on the structure and property of polycarbonate/polypropylene alloys

Abstract: Polycarbonate/Polypropylene (PC/PP) alloy is a typical thermodynamically incompatible system. In this work, ethylene‐methyl acrylate copolymer (EMA), methoxamine hydrochloride‐grafted POE (POE‐g‐MAH), ethylene‐butyl acrylate‐glycidyl methacrylate copolymer (EAY), a self‐made compatibilizer (PPM‐g‐GMA) of a mixture of glycidyl methacrylate grafted PP (PP‐g‐GMA) and glycidyl methacrylate‐grafted POE (POE‐g‐GMA) were selected as compatibilizer to prepare PC/PP alloys with the mass ratio of 65:30. Systematical stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…on polymers under melt-blending, forming robust and stable covalent bonds. [24] Zhou et al [25] added POEg-GMA to PLA/poly (propylene carbonate) blends, and found that elongation at break and impact strength increased by 26.94% and 95.67%. Pan et al [26] improved the compatibility of poly(ethylene terephthalate)/highdensity polyethylene (PET/HDPE) blends by adding POE-g-GMA, and found that the impact strength increased from 44.8 J/m to 110.8 J/m.…”
Section: Introductionmentioning
confidence: 99%
“…on polymers under melt-blending, forming robust and stable covalent bonds. [24] Zhou et al [25] added POEg-GMA to PLA/poly (propylene carbonate) blends, and found that elongation at break and impact strength increased by 26.94% and 95.67%. Pan et al [26] improved the compatibility of poly(ethylene terephthalate)/highdensity polyethylene (PET/HDPE) blends by adding POE-g-GMA, and found that the impact strength increased from 44.8 J/m to 110.8 J/m.…”
Section: Introductionmentioning
confidence: 99%